Na noite do ventre, o diamante, de Moacyr Scliar : transculturalidade e exílio de si mesmo - Mader, Eneida Aparecida (2014)
This dissertation sought to focus on Moacyr Scliar‟s literary writing, more specifically on the novel In the night of the venter, the diamond, the boundaries of the ethnic lathing and to check how the narrative presents a mingled view between foreigner and Brazilian (Jewish / non-Jewish), and, also, how a literary text revisits, under a new prism, diversified cultural aspects, referring to Brazil and to the foreigner‟s culture. This research will guide the focus on this twofold perception of the other and of himself, from the non-Jewish to the Jewish and vice-versa, in an arc that goes from the stereotype to its possible breakdown. In order to compose this trajectory, Moacyr Scliar will be part of a contemporary era, as it provides, in the narrative quoted, the transit of multiple cultures, the trajectory of the characters‟ running away (internal exile), the resignification of the memorialistic and historical past, resulting in a reterritorialized cultural identity. For the research, we especially resorted to theoretical contributions of Zilá Bernd, Berta Waldman, Julia Kristeva, Aleida Assmann, Paul Ricoeur, Gilles Deleuze and Félix Guattari.